Perlindungan Hukum Bagi Penyandang Disabilitas Dalam Mendapatkan Pekerjaan Berdasarkan International Covenant On Economic Social And Cultural Rights 1966 Dan Undang-Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan - Budi Ardianto; Mochammad Farisi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
Legal protection in getting a job is the right of everyone, including persons with disabilities. This study aims to find out how legal protection for persons with disabilities in getting a job and to find out how international law and national law protect persons with disabilities in getting a job. The problem in this study is that people with disabilities are considered unfit for decent work with non-disabilities. This violates the contents of the ICESCR 1966 in Article 6 and Law Number 13 of 2003 concerning Manpower, Article 67. Both articles clearly state the right of everyone to freely choose and be elected in terms of employment. However, legal protection obtained by persons with disabilities in getting a job has not been fully realized. The type of research used in the research used in this research is normative juridical research or literature law research. Through normative research, this research focuses on answering the following problems: 1) How is the arrangement of persons with disabilities according to international and national law. 2) Whether existing laws provide protection for persons with disabilities in obtaining the right to work.